Comments on Skin Effect in Solitary Solid Tubular Conductor - Oldřich Coufal (Advances in Mathematical Physics)
J. C. Maxwell derived formulae for the calculation of current density and current in a cylindrical conductor supplied with variable current. In the 1950s K. Simonyi published a method for calculating current density in a cylindrical conductor made up of two conductors, cylindrical and tubular, of different resistivities. The present paper proves that Simonyi's result is incorrect. The main attention is devoted to the method of calculating current density in a tubular conductor made up of tubular conductors of different resistivities.